Case reportThe development of squamous cell carcinoma in a patient after kidney transplantation: a case report - Witmanowski, Henryk; Lewandowska, Małgorzata; Szychta, Paweł; Sporny, Stanisław; Rykała, Jan (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
In patients with organ transplantation as compared to the general population the risk of cancer is significantly increased. The most common changes are malignant tumors of the skin, constituting 30-65% of malignant tumors found in recipients. Potential risk factors for skin cancer after a transplant operation are: solar radiation, immunosuppressive therapy, genetic factors, infection with HPV and skin cancer transmission before transplantation. In contrast to the immunocompetent population, skin cancers in transplant recipients are dominated by squamous cell carcinoma, followed by basal cell carcinoma. Squamous cell carcinoma in patients after transplantation is characterized by a strong tendency to give local recurrences and distant metastases. Due to the high risk of developing skin cancer in transplant recipients, preventive oncology plays an important role in the long-term care of patients after transplantation. This includes: sun protection, education, and early treatment of patients with precancerous lesions. It is also stressed that systematic dermatologic studies need to be carried out in patients after transplantation surgery. The paper contains basic information about skin cancers in organ transplant recipients: epidemiology, potential risk factors, treatment and prognosis. The paper presents also a case of patient who developed squamous cell carcinoma of the skin 3 years after renal transplantation.